Modern Times: Temporality and Genres of Interwar Modernism. - Flynn, Nicole. (2017)
Abstract: This dissertation explores how new ideas about time, as both public force and private experience, shaped literary form in England between the two World Wars. The texts I examine demonstrate that these dramatic changes in the understanding and organization of time unsettled generic categories. As modernist authors attempted to regain their balance in the wake of this temporal and formal upheaval, they had to negotiate the private and public realms of time, to redefine the genre in which they were writing or to create a new genre altogether. In my argument, private time is aligned with the traditional modernist focus on individual subjectivity, the personal experience of time, and techniques such as stream of consciousness narration. Public time is aligned with power structures, with global, homogenizing forces, often symbolized by the clock. There is a productive tension between these two polarities and an exclusive focus on the personal leads to a falsely positive assessment of literature's productive relationship with temporality. I argue that we get a more accurate image of the ways in which temporality and text function together when we bring genre into the picture. Each of my chapters focus on texts from a different genre: Jean Rhys's interwar novels, D.H. Lawrence's nonfiction essays and London's musical revues. All of these texts demonstrate the constitutive connection between temporality and genre. By reading them, we witness the deep formal consequences on interwar literary and theatrical productions brought on by seismic shifts in the understanding and experience of time.; Thesis (Ph.D.)--Tufts University, 2012.; Submitted to the Dept. of English.; Advisor: Virginia Jackson.; Committee: Martin Harries, Ichiro Takayoshi, and John Lurz.; Keywords: Literature, British and Irish literature, and Theater.